Soft skill competency and employees' capacity as the intervening factors between training effectiveness and health workers' performance - Hasmin Tamsah; Gunawan Bata Ilyas; Jumiaty Nurung; Ekafadly Jusuf; Sri Rahmi (Cogent Business & Management, 2023)
This study aimed to determine the role of soft skill competency (SSC) and employees' capacity (EC) in mediating the effect of training effectiveness (TE) on health workers' performance (HWP). A quantitative approach was conducted by using the Structural Equation Modeling (SEM)-Amos version 23 analysis, with data obtained through accidental sampling from 222 health workers who filled out online questionnaires and were declared complete. The results showed that TE improved SSC and HWP, although it did not have a direct effect on increasing EC. This indicated that SSC was needed to mediate the relationship between these two variables. SSC and EC also mediated the effect of TE on HWP. These results were expected to enrich the limited references in explaining the relationship between human resources (HR) planning and HWP, specifically during the COVID-19 pandemic.
Keywords: 650; employees’ capacity; health workers’ performance; soft skill competency; training effectiveness